2012
DOI: 10.1016/j.foodcont.2011.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Microbial quality and yeast population dynamics in cracked green table olives’ fermentations

Abstract: Please cite this article as: Alves, M., Gonçalves, T., Quintas, Célia. Microbial quality and yeast population dynamics in cracked green table olives ' fermentations, Food Control (2011), doi: 10.1016/ j.foodcont.2011 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 31 publications
6
40
0
Order By: Relevance
“…The behaviour of yeasts was in good agreement with previous published works in olive brines (Alves, Gonçalves, & Quintas, 2012;Arroyo-López, Querol, Bautista-Gallego, & Garrido-Fernández, 2008 Means ± SD of three replicates, n = 24. Means followed by the same letter in the same micro-organism are not significantly different (p < 0.05).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The behaviour of yeasts was in good agreement with previous published works in olive brines (Alves, Gonçalves, & Quintas, 2012;Arroyo-López, Querol, Bautista-Gallego, & Garrido-Fernández, 2008 Means ± SD of three replicates, n = 24. Means followed by the same letter in the same micro-organism are not significantly different (p < 0.05).…”
Section: Resultssupporting
confidence: 90%
“…Moreover, several yeasts were obtained directly from natural black olive fermentations (Coton, Coton, Levert, Casaregola, & Sohier, 2006;Nisiotou, Chorianopoulos, Nychas, & Panagou, 2010) and green table olive fermentations (Bautista-Gallego et al, 2011). Therefore, it was reported that yeasts were the most relevant micro-organisms in the fermentation of cracked green table olives (Alves et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Although found in less number, the yeasts C. tropicalis and S. cerevisiae were also present in olive pulp; whereas in brine was additionally verified the presence of Pichia manshurica. The presence of C. boidinii in brines was previously described in the early (Alves et al, 2012) and later phase (Bautista-Gallego et al, 2011) of the fermentation of various table olives types, as well as in all fermentation phases of natural black olives (Nisiotou et al, 2010). This specie showed to exhibit lipase activity (Bautista-Gallego et al, 2011), contributing to improve the flavor of olives through the formation of esters from free fatty acids of the fruit (Hern andez et al, 2007;Rodríguez-G omez et al, 2010).…”
Section: Yeast Dynamics During Fermentationmentioning
confidence: 76%
“…[8], researchers studied the yeast population associated with Portuguese brined green olives of cultivars Galega and Cordovil, fermentation was mainly driven by P. membranifaciens, P. fermentans, S. cerevisiae and C. oleophila. In a similar work [59], it has been found that during the initial phases of cracked green Manzanilla olive fermentation a great diversity of yeasts was observed; however, as the process was evolving, the biodiver sity decreased with the fermentative yeasts Citeromyces matritensis, Zygotorulaspora mrakii and S. cerevisiae becoming the dominant species. These species though are reported as high risk spoilage microorganisms contrary to P. membranifaciens reported by [8].…”
Section: Portugalmentioning
confidence: 84%